Cochlear implants in children: principles, practice and predictions. - O'Donoghue, G M (1996)
An audit was undertaken of the first 36 children who had received cochlear implants in Nottingham. These children had previously derived no benefit from prolonged trials of powerful hearing aids. Following implantation, all children could hear warble tones at all audiometric frequencies from 500 to 4000 Hz at sound pressure levels between 30 and 50 dB. The majority of children implanted below the age of 5 years developed intelligible spoken language after 3 years. The outcomes for children born deaf and those who acquired deafness under the age of 3 years were substantially similar. The best results were obtained in those children who were implanted before the age of 5 years or in whom the deafness was of short duration. The needs of implanted children continue over many years. A small number of dedicated, well-funded multidisciplinary teams are needed to meet the growing demand nationally.